Category «informing» («richness») of content, its expression in a text (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2011)
The article continues the row of publications of author, devoted to the theory of text. The category of informing is exposed as sign of artistic and inartistic texts, certain its signs and linguistic expression in a text structure.
Keywords: richness of content; informing; implication; variety of information; category of text